Sulit Mengungkapkan Emosi: Kecerdasan Emosi Dan Attachment Style Dengan Alexithymia Pada Generasi Z - Marisalia -; Faisal Adnan Reza; Annisa Fitriani (unprimdn.ac.id, 2024)
Generation Z is a generation that is prone to mental health problems caused by poor social relationships and emotions. One of the mental health problems experienced by Generation Z is alexithymia. This happens because not all individuals can identify, describe, and express their emotions. Therefore, this study was conducted to determine the relationship between emotional intelligence and attachment style with alexithymia in Generation Z. The method used in this research is a quantitative approach method, with research sampling using a purposive sampling technique. The sample used in this study is Generation Z, with a vulnerable age of 15-19 years, who are in high school (SMA), and as many as 100 respondents. Then, the researcher used multiple linear regression test techniques to analyze the data. The results obtained from this study indicate that the variables of emotional intelligence and attachment style have a negative-significant effect on the alexithymia variable with an R-value of 0.697, R-square of 0.485 with an F value of 45.736 and a P-value of <0.001 (p<0.001). The higher the emotional intelligence and attachment style, the lower the alexithymia and vice versa.